Sinus of Valsalva aneurysm ruptured to the right atrium in the adult: a case report - Carrión-Arcela, Jean Pierre (2021)
Rupture of a Valsalva aneurysm in the adult is extremely rare and is often complicated by acute heart failure. We present the case of a 39-year-old patient with a non-coronary sinus of Valsalva aneurysm complicated by rupture to the right atrium associated with severe aortic regurgitation and moderate tricuspid regurgitation. The treatment was surgical and was based on the repair with a pericardial patch over the aneurysm, aortic valve replacement, and tricuspid plasty. We emphasize the importance of an early diagnosis and timely surgical treatment due to the high associated mortality.